The Pathogenic Role of NLRP3 Inflammasome Activation in Inflammatory Bowel Diseases of Both Mice and Humans - Liu, Ling (J Crohns Colitis, 2017)
BACKGROUND AND AIMS: NLRP3 inflammasome is known to be involved in inflammatory bowel diseases. However, it is controversial whether it is pathogenic or beneficial. This study evaluated the roles of NLRP3 inflammasome in the pathogenesis of inflammatory bowel disease in IL-10(-/-) mice and humans. METHODS: NLRP3 inflammasome in colonic mucosa, macrophages, and colonic epithelial cells were analysed by western blotting. The NLRP3 inflammasome components were studied by sucrose density gradient fractionation, chemical cross-linking, and co-immunoprecipitation. The role of NLPR3 inflammasome in the pathogenesis of colitis was extensively evaluated in IL-10(-/-) mice, using a specific NLPR3 inflammasome inhibitor glyburide. RESULTS: NLRP3 inflammasome was upregulated in colonic mucosa of both IL-10(-/-) mice and Crohn’s patients. NLRP3 inflammasome activity in IL-10(-/-) mice was elevated prior to colitis onset; it progressively increased as disease worsened and peaked as macroscopic disease emerged. NLRP3 inflammasome was found in both intestinal epithelial cells and colonic macrophages, as a large complex with a molecular weight of ≥ 360 kDa in size. In the absence of IL-10, NLRP3 inflammasome was spontaneously active and more robustly responsive when activated by LPS and nigericin. Glyburide markedly suppressed NLRP3 inflammasome expression/activation in IL-10(-/-) mice, leading to not only alleviation of ongoing colitis but also prevention/delay of disease onset. Glyburide also effectively inhibited the release of proinflammatory cytokines/chemokines by mucosal explants from Crohn’s patients. CONCLUSIONS: Abnormal activation of NLRP3 inflammasome plays a major pathogenic role in the development of chronic colitis in IL-10(-/-) mice and humans. Glyburide, an FDA-approved drug, may have great potential in the management of inflammatory bowel diseases.